The Effect of Audit Tenure and Audit Opinion on Audit Report Lag: A Study of Indonesian Manufacturing Companies - Muhammad Ashar; A. Anggi Reskiamalia; A. Amiruddin; S. Syamsuddin (Golden Ratio of Auditing Research, 2026)
This study examines the impact of audit tenure and opinion on audit report lag in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). Audit report lag is a crucial measure of the timeliness of financial reporting, yet prior studies show inconsistent findings regarding its relationship with audit tenure and audit opinion. This study addresses that gap by focusing on a specific industry sector in Indonesia. A quantitative method was employed, using secondary data obtained from the audited financial statements of selected companies between 2020 and 2024. The sampling technique was purposive, resulting in six companies as research samples. The independent variables are audit tenure and opinion, while the dependent variable is audit report lag. The data collection method used is documentation. Data were analyzed using classical assumption testing and multiple linear regression, with hypothesis testing performed through SPSS 27. The hypotheses tested in this study are as follows: (H1) It is suspected that audit tenure and audit opinion simultaneously affect audit report lag in manufacturing companies listed on the IDX; (H2) It is suspected that audit tenure and audit opinion partially affect audit report lag in manufacturing companies listed on the IDX; (H3) One of the variables has a dominant effect on audit report lag in manufacturing companies listed on the IDX.